2020
DOI: 10.3389/fphar.2020.583171
|View full text |Cite
|
Sign up to set email alerts
|

Tripterygium Ingredients for Pathogenicity Cells in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease mainly characterized by chronic polyarthritis. Many types of cells play pivotal roles in the pathogenicity of RA, such as T cells, B cells, macrophages, dendritic cells (DCs), osteoclasts (OCs), and fibroblast-like synoviocytes (FLS). Tripterygium wilfordii Hook f. (TwHf) and its ingredients are able to control disease activity by regulating the functions of cells mentioned above, and the clinical studies have highlighted the importance of TwHf ingredients in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 97 publications
(99 reference statements)
1
14
0
Order By: Relevance
“…Some of these trials have even indicated that TWG may achieve better effectiveness than DMARDs monotherapy in patients with RA [ 20 ], but multi-organ toxicity and diverse side-effects of TWG have been reported [ 21 ]. The anti-rheumatic efficacy of TWG is based on immunosuppression, anti-inflammation, anti-angiogenesis, and bone and cartilage protection activities, due to reduced expression of proinflammatory cytokines and PGs, adhesion molecules and matrix metalloproteinases by macrophages, lymphocytes, synovial fibroblasts and chondrocytes [ 21 , 22 ], but the precise mechanisms of action are still obscure and await more detailed explorations. Triptolide and celastrol are the predominant constituents of TWG, accounting for the pharmacological features as well as for the reported toxicity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these trials have even indicated that TWG may achieve better effectiveness than DMARDs monotherapy in patients with RA [ 20 ], but multi-organ toxicity and diverse side-effects of TWG have been reported [ 21 ]. The anti-rheumatic efficacy of TWG is based on immunosuppression, anti-inflammation, anti-angiogenesis, and bone and cartilage protection activities, due to reduced expression of proinflammatory cytokines and PGs, adhesion molecules and matrix metalloproteinases by macrophages, lymphocytes, synovial fibroblasts and chondrocytes [ 21 , 22 ], but the precise mechanisms of action are still obscure and await more detailed explorations. Triptolide and celastrol are the predominant constituents of TWG, accounting for the pharmacological features as well as for the reported toxicity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Icariin inhibited STAT3 activation in T cells, resulting in decreased IL-17 production and alleviated RA [ 51 ]. Moreover, IL-6, IL-1 β , and TNF- α were vital pathogenicity cytokines, which could be reduced by components of TH [ 52 , 53 , 55 ]. Other involved chemokines included CCLs and CXCLs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…rough UHPLC-Q-TOF/MS analysis, 67 chemical constituents were identified from the 70% methanol-in-water extract of KC according to mass fragmentation patterns based on a previously established KC-specified in-house library (Figure 1). Among them, 43 compounds (1,2,3,4,5,8,10,11,15,16,17,18,19,20,21,22,23,25,26,27,28,29,30,31,32,33,34,35,37,43,45,47,48,50,51,52,55,58, 60, 63, 64, 66, and 67) were authenticated by comparison to the mass spectrums of the corresponding chemical standards, as indicated by a star symbol ( * ) in Table S1.…”
Section: Identification Of the Chemical Constituents In Kc Extract By Uhplc-q-tof/msmentioning
confidence: 99%
“…RA-FLSs are a key component of this invasive synovium and have a major role in the initiation and perpetuation of destructive joint in ammation [45]. RA-FLS releases important in ammatory cytokines (TNF-a, IL-1b, IL-6, IL-21, IL-22, and IL-32), chemokines (CXCL1, CXCL5, MCP-1, G-CSF, and IL-8) and In ammatory mediators (TLR-2, TLR-3, TLR-4, iNOS, and COX-2), which promotes the in ltration of monocytes, macrophages, neutrophils, DCs, T cells, and B cells into joints and results in chronic in ammation and joint destruction [44]. Studies in recent years have demonstrated that the mammalian target of rapamycin/p70 ribosomal protein S6 kinase (mTOR/p70S6K) signaling pathway is over-activated in RA-FLSs, which plays an important role in regulating cell apoptosis and survival, as in Fig.…”
Section: The Proliferation Inhibition Effect On Ra-flss In Vitro Studymentioning
confidence: 99%